2018
DOI: 10.1002/anie.201805212
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Initiated and Regulated Controlled Radical Polymerization under Ambient Conditions

Abstract: A rapid oxygen-initiated and -regulated controlled radical polymerization was conducted under ambient temperature and atmosphere. The reaction between triethylborane and oxygen provides ethyl radicals, which initiate and mediate the radical polymerization. The controlled radical polymerization was achieved using RAFT chain transfer agents (CTA) without any process of removing oxygen, providing well-defined polymers with almost full conversion (>95 %) in a short period (15 min). High-throughput screening was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 48 publications
0
68
0
Order By: Relevance
“…The M n (NMR) is calculated by the degree of polymerization (DP). 31,32 The ratio of the peak areas between 3.80 and 3.50 ppm and 7.23 and 6.26 ppm is 4.77. Therefore, the total DP for the PS block is 446.…”
Section: Resultsmentioning
confidence: 99%
“…The M n (NMR) is calculated by the degree of polymerization (DP). 31,32 The ratio of the peak areas between 3.80 and 3.50 ppm and 7.23 and 6.26 ppm is 4.77. Therefore, the total DP for the PS block is 446.…”
Section: Resultsmentioning
confidence: 99%
“…43 The combination of TEB and oxygen was simply used to overcome the oxygen inhibition in RAFT polymerization. 44 The polymerization of MA in DMSO with RAFT chain-transfer agent and TEB reached >95% conversion and provided well-defined polymers under ambient atmosphere and temperature after 15 min. In a control experiment conducted in nitrogen atmosphere, no monomer conversion was observed after 1 h reaction.…”
Section: Figurementioning
confidence: 96%
“…Various oxygen‐tolerated CRPs were developed based on transforming oxygen molecule to other non‐initiating compounds . The combination of TEB and oxygen was simply used to overcome the oxygen inhibition in RAFT polymerization . The polymerization of MA in DMSO with RAFT chain‐transfer agent and TEB reached >95% conversion and provided well‐defined polymers under ambient atmosphere and temperature after 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In the last case, the consumption of oxygen has been reported at room-temperature using three RAFT initiation systems via the Fenton reaction (and related processes), [28,30] acid catalyzed reactions of ketones and hydroperoxides, [27] and autoxidation of alkylboranes. [29,31] To the best of our knowledge, the application of these RAFT initiation systems for the synthesis of star polymers in the presence of oxygen has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…[17,[32][33][34] Later, Pan and coworkers found similar success initiating RAFT polymerization by directly employing uncomplexed trialkylborane, which the authors demonstrated to be compatible with a smallvolume/high-throughput screening process in ambient conditions and an externally regulated polymerization system that could be switched "on" and "off" through intermittent injections of air. [31] Most recently, Feng and coworkers demonstrated the use of trialkylboranes as a potent means for chain transfer agent removal from RAFT-derived polymers, achieving complete removal within minutes under ambient conditions for a broad range of chain transfer agents. [35] Descriptions of these alkylborane processes for RAFT and other polymerizations have been summarized in a recent mini-review.…”
Section: Introductionmentioning
confidence: 99%